2013
DOI: 10.3109/08958378.2013.793439
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity evaluation of electronic cigarette vapor extract on cultured mammalian fibroblasts (ClearStream-LIFE): comparison with tobacco cigarette smoke extract

Abstract: This study indicates that EC vapor is significantly less cytotoxic compared tobacco CS. These results should be validated by clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
130
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(151 citation statements)
references
References 47 publications
15
130
0
5
Order By: Relevance
“…In fact, the Flavors and Extracts Manufacturers' Association (FEMA) has issued an official statement mentioning that flavor ingredients are evaluated for exposure through ingestion only; thus, any results cannot be extrapolated to use through inhalation. 5 Studies have shown that any cytotoxic properties of e-cigarette liquids and aerosol, although significantly lower than tobacco smoke, may be attributed to specific flavors, [6][7][8] indicating that further research is certainly needed in this area.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the Flavors and Extracts Manufacturers' Association (FEMA) has issued an official statement mentioning that flavor ingredients are evaluated for exposure through ingestion only; thus, any results cannot be extrapolated to use through inhalation. 5 Studies have shown that any cytotoxic properties of e-cigarette liquids and aerosol, although significantly lower than tobacco smoke, may be attributed to specific flavors, [6][7][8] indicating that further research is certainly needed in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Romagna and his group report that in vitro, e-cigarette vapor is significantly less toxic than tobacco smoke [11]. This is not unexpected given the thousands of known chemical and toxins known to be in tobacco smoke.…”
Section: Discussionmentioning
confidence: 88%
“…But again, flavoured e-liquid was the most cytotoxic in the group. It was coffee flavoured solution [18]. In another study, which also evaluated cytotoxicity of various e-liquids, the most distinctive was that of cinnamon and cookies flavour [19].…”
Section: The Chemical Composition Of Electronic Cigarettes Their Toxmentioning
confidence: 99%